Preparation method and application of hydrogen-eliminating and oxygen-evolving electrode
By plating gold on the titanium mesh and constructing a diffusion electrode with platinum-loaded iridium oxide, the problem of excessive hydrogen concentration in oxygen during the electrolytic water hydrogen production process is solved, and low-cost, low-oxygen hydrogen and high-stability electrodes are achieved, avoiding thermal damage.
Patent Information
- Application Number
- CN202510039524.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-04
AI Technical Summary
During the process of electrolyzing hydrogen production, the concentration of hydrogen in the oxygen generated by the anode is too high, which may lead to the risk of explosion. In the prior art, the addition of platinum layers or catalysts is costly and has poor stability.
Gold plated on the titanium mesh and constructed a diffusion electrode with platinum-loaded iridium oxide. The high potential oxidation resistance and conductivity of the titanium mesh are improved through the gold plating layer. The platinum particles are dispersed on the surface of the titanium mesh to eliminate hydrogen in oxygen, and the iridium oxide layer enhances the oxygen precipitation activity of the catalyst.
A low-cost, low-oxygen electrode is achieved, which improves the durability and stability of the electrode, and avoids thermal damage caused by direct reaction between hydrogen and oxygen.
Smart Images

Figure CN119753750A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water electrolysis and relates to a preparation method and application of a hydrogen-eliminating and oxygen-evolving electrode. Background Art
[0002] With the development of hydrogen energy, the hydrogen end has put forward higher requirements for the quality of hydrogen. As one of the most important means of preparing green hydrogen, water electrolysis has attracted much attention from all over the world. However, the need to use an efficient and highly stable oxygen evolution catalyst in the water electrolysis process is one of the important challenges currently faced. PEM water electrolysis is one of the most promising green hydrogen preparation technologies, which has the advantages of high current density, high efficiency, fast response, small size, low internal resistance, and wide adaptability. During the water electrolysis process, the hydrogen produced by the cathode will diffuse and penetrate into the anode through the PEM, resulting in excessive hydrogen concentration in the oxygen produced by the anode. If the concentration exceeds 4%, there will be a risk of explosion. Therefore, it is particularly important to reduce the hydrogen content in the anode oxygen. At present, there are mainly platinum layers added to the PEM or platinum added to the catalytic layer to eliminate the hydrogen content in the oxygen, but the difficulty is relatively large and the cost is high. In view of the problems existing in the above-mentioned prior art, the present invention designs a diffusion electrode with gold plating and platinum-loaded iridium oxide on a titanium mesh, which is expected to achieve low cost, low oxygen hydrogen and high stability. Summary of the invention
[0003] The object of the present invention is to provide a preparation method of a hydrogen-eliminating and oxygen-evolving electrode and its application, which improves the durability of the electrode and can reduce the hydrogen content in oxygen.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a hydrogen-evolving electrode, wherein the specific process of the method for preparing the hydrogen-evolving electrode is as follows:
[0006] S1: Titanium mesh surface pretreatment
[0007] The titanium mesh is placed in a mixed acid solution and soaked for 1 to 5 minutes, taken out after soaking, the acid solution on the surface is washed off with deionized water, and the cleaned titanium mesh is placed in an argon atmosphere to obtain a titanium mesh after surface pretreatment;
[0008] S2: Titanium mesh gold-plated
[0009] Chloroauric acid is dissolved in dimethylformamide (DMF), and a perchlorate with a concentration of 0.1 to 0.5 mmol / L is added to obtain a first electrolyte solution. The titanium mesh with surface pretreatment in S1 is used as a cathode, a highly graphitized carbon rod is used as a counter electrode, and an Ag / AgCl electrode is used as a reference electrode. The first electrolyte solution is deposited by constant potential electrodeposition to obtain a titanium mesh Au-Timesh with gold on the surface.
[0010] S3: Gold-plated titanium mesh with platinum diffusion
[0011] Dissolve chloroplatinic acid in dimethylformamide (DMF), and add perchlorate with a concentration of 0.1-0.5 mol / L to obtain a second electrolyte solution, use the gold-plated titanium mesh Au-Ti mesh prepared by S2 as a cathode, a highly graphitized carbon rod as a counter electrode, and an Ag / AgCl electrode as a reference electrode, and use constant potential electrodeposition of the second electrolyte solution to obtain a gold-plated titanium mesh Pt / Au-Ti mesh with dispersed platinum.
[0012] S4: Surface coating with iridium oxide
[0013] Dissolve chloroiridic acid in deionized water to obtain a chloroiridic acid solution with a concentration of 0.01-0.1 mol / L, then adjust the pH value to 10-14 with sodium hydroxide with a concentration of 1 mol / L, and continue stirring for 30-90 min to obtain a third electrolyte. Use the gold-plated titanium mesh Pt / Au-Ti mesh with platinum dispersed distribution prepared by S3 as an anode, a highly graphitized carbon rod as a counter electrode, and an Ag / AgCl electrode as a reference electrode. Use a trapezoidal wave potential to perform electrodeposition treatment of the third electrolyte, control the upper and lower limits of the potential and the number of scanning cycles, and obtain a gold-plated titanium mesh electrode IrO2 loaded with platinum dispersed distribution and iridium oxide. x / Pt / Au-Ti mesh, that is, IrO x / Pt / Au-Ti mesh hydrogen and oxygen evolution electrode, the prepared IrO x The thickness of the gold-plated layer on the titanium mesh surface in the / Pt / Au-Ti mesh hydrogen-evolution electrode is 1-5 μm, the size of the dispersed platinum particles is 0.1-2 μm, and the size of the surface iridium oxide particles is 2-10 nm.
[0014] Furthermore, the mixed acid solution in S1 is a mixed solution of nitric acid and hydrofluoric acid, the molar ratio of nitric acid to hydrofluoric acid is 1:1 to 10:1, and the hydrogen ion concentration in the mixed acid is 0.1 to 0.5 mol / L.
[0015] Furthermore, the concentration of chloroauric acid in DMF in S2 is 0.5-5 mmol / L.
[0016] Furthermore, the perchlorate in S2 is one or more of potassium perchlorate, sodium perchlorate, and lithium perchlorate.
[0017] Furthermore, the constant potential electrodeposition parameters in S2 are: potential -1.2 to -1.5 V vs. Ag / AgCl, and electrodeposition time 30 to 60 min.
[0018] Furthermore, the concentration of chloroplatinic acid in DMF in S3 is 0.1-2 mmol / L.
[0019] Furthermore, the perchlorate in S3 is one or more of potassium perchlorate, sodium perchlorate, and lithium perchlorate.
[0020] Furthermore, the constant potential electrodeposition parameters in S3 are: potential -1.5 to -1.8 V vs. Ag / AgCl, and electrodeposition time 10 to 30 min.
[0021] Furthermore, in S4, the lower limit potential range of the trapezoidal wave is 0.1-0.5V, the upper limit potential range is 0.8-1.8V, the voltage rise rate is 0.02-0.2V / s, the upper and lower limit potential constant potential time is 5-30s, and the number of trapezoidal wave scanning circles is 50-200 circles.
[0022] An application of a hydrogen-eliminating and oxygen-evolving electrode, wherein the hydrogen-eliminating and oxygen-evolving electrode is applied to electrolyzing water.
[0023] In the PEM water electrolysis membrane electrode, the proton conductivity of the PEM membrane is low, which contributes to most of the impedance. The impedance of the membrane is positively correlated with its thickness. The thicker the thickness, the greater the impedance of the membrane; the thinner the thickness, the smaller the impedance of the membrane. Therefore, with the development of technology, one way for the PEM water electrolysis membrane electrode to achieve high efficiency is to make the PEM membrane thinner and thinner. However, as the PEM membrane becomes thinner, the permeation of hydrogen and oxygen will also increase. The diffusion of hydrogen from the cathode to the anode causes the hydrogen concentration in the oxygen to increase. If the concentration increases to the explosion limit of hydrogen, it will cause more serious safety problems. Therefore, how to eliminate the concentration of hydrogen in the anode oxygen will become very important.
[0024] The present invention constructs a hydrogen removal function by plating gold and platinum on the surface of the titanium mesh. The gold layer is first plated on the surface of the Ti mesh, which is beneficial to improving the high-potential oxidation resistance of the Ti mesh. At the same time, the gold plating can further improve the conductivity of the electrode and reduce the interface impedance. The platinum particles dispersed on the surface of the Au layer mainly function to remove hydrogen. The basic principle is that when the hydrogen diffuses from the cathode to the anode and passes through the titanium mesh together with oxygen, the hydrogen and oxygen will catalyze the reaction on the platinum surface to directly produce water and consume the hydrogen, thereby achieving the purpose of reducing the hydrogen in the oxygen. At the same time, iridium oxide on the gold and platinum surfaces helps to enhance the IrO x conductivity and improve the oxygen evolution activity of the catalyst.
[0025] The present invention is different from the traditional hydrogen elimination process: adding platinum to the PEM membrane or to the catalyst layer, because the direct reaction of hydrogen and oxygen on the platinum surface will release heat, long-term operation will cause the membrane and the catalyst layer to decay significantly. The present invention first removes the oxide on the surface of the Ti mesh, and electro-deposit an Au layer to protect the titanium mesh and improve its high-potential corrosion resistance and conductivity. By controlling the potential and time, the thickness of the Au layer can be controlled; then, by electro-depositing platinum particles of appropriate particle size dispersed on the surface of the Au layer, the purpose of eliminating hydrogen in oxygen is achieved. By controlling the potential and time, the size and distribution of the platinum particles can be controlled; finally, an iridium oxide layer is electro-deposited on the electrode surface to play a role in oxygen precipitation. Au and Pt can improve the conductivity of iridium oxide, further enhancing the OER catalytic activity of the electrode.
[0026] Beneficial effects of the present invention:
[0027] The hydrogen removal function is constructed by plating gold and platinum on the surface of the titanium mesh. Plating the gold layer on the Ti surface first is beneficial to improving the high-potential oxidation resistance of the Ti mesh. At the same time, gold plating can further improve the conductivity of the electrode and reduce the interface impedance; the platinum particles dispersed on the surface of the Au layer mainly function to remove hydrogen. The basic principle is that when the hydrogen diffuses from the cathode to the anode passes through the titanium mesh together with oxygen, the hydrogen and oxygen will catalytically react on the platinum surface to directly produce water and consume the hydrogen, thereby achieving the purpose of reducing the hydrogen in the oxygen. It avoids adding platinum directly to the PEM membrane or to the catalytic layer. Since the reaction of hydrogen and oxygen directly on the platinum surface will release heat, long-term operation will cause a substantial attenuation of the membrane and the catalytic layer. At the same time, iridium oxide on the gold and platinum surfaces helps to enhance the IrO x conductivity, thereby improving the oxygen evolution activity and durability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0029] Figure 1 This is the trapezoidal wave potential program diagram of the electrodeposition of iridium oxide on the gold-plated titanium mesh with platinum dispersion;
[0030] Figure 2 The oxygen evolution polarization performance of the electrodes of Example 4 and Comparative Example 1;
[0031] Figure 3 The percentage of hydrogen in the anode oxygen during the electrolysis of water in each embodiment and comparative example. DETAILED DESCRIPTION
[0032] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0033] Example 1
[0034] S1: Take 9.130g of 69% concentrated nitric acid and 0.5g of 40% hydrofluoric acid and dissolve them in 1L of deionized water. The molar ratio of nitric acid to hydrofluoric acid is 10:1. Immerse a 5cm×5cm Ti mesh in the mixed acid for 2min. Then, wash the acid solution on the surface of the Ti mesh with 100mL of deionized water for 3 times and blow dry with argon. Place the Ti mesh with oxide removed in an argon protective atmosphere for standby use.
[0035] S2: Weigh 0.412g of tetrahydrate chloroauric acid and dissolve it in 1L of DMF with a concentration of 1mmol / L, add 13.9g of potassium perchlorate with a concentration of 0.1mol / L to form the first electrolyte solution, then insert the Ti mesh with oxide removed as a cathode into the first electrolyte solution, use a highly graphitized carbon rod as a counter electrode, and use an Ag / AgCl electrode as a reference electrode, and use a constant potential electrodeposition of the first electrolyte solution, with a constant potential of -1.5V vs.Ag / AgCl, and an electrodeposition time of 30min to obtain a titanium mesh Au-Ti mesh with gold plated on the surface;
[0036] S3: Weigh 0.0517g of chloroplatinic acid hexahydrate and dissolve it in 1L of DMF at a concentration of 0.1mmol / L; add 13.9g of potassium perchlorate at a concentration of 0.1mol / L, use Au-Ti mesh as cathode, highly graphitized carbon rod as counter electrode, Ag / AgCl electrode as reference electrode, and use constant potential electrodeposition of the second electrolyte solution. The constant potential is -1.8V vs.Ag / AgCl, and the electrodeposition time is 10min to obtain Pt / Au-Ti mesh with dispersed platinum.
[0037] S4: Weigh 4.07 g of hexahydrated iridium chloride and dissolve it in 1 L of deionized water. The concentration of iridium chloride is 0.01 mol / L. Then adjust the pH value of the solution to 12 with 1 mol / L sodium hydroxide solution. Stir continuously for 60 min to obtain a third electrolyte. Use a gold-plated titanium mesh Pt / Au-Ti mesh with a dispersed platinum distribution as an anode, a highly graphitized carbon rod as a counter electrode, and an Ag / AgCl electrode as a reference electrode. Use a trapezoidal wave potential to electrodeposit the third electrolyte. Control the lower limit potential of the trapezoidal wave to 0.5 V, the upper limit potential to 1.5 V, the voltage rise rate to 0.1 V / s, the upper limit potential constant potential time to 10 s, the lower limit potential constant potential time to 10 s, and the number of trapezoidal wave scanning circles to 100 circles to obtain a gold-plated titanium mesh electrode IrO2 loaded with iridium oxide and dispersed platinum distribution. x / Pt / Au-Ti mesh, that is, IrO x / Pt / Au-Ti mesh hydrogen elimination and oxygen evolution electrode.
[0038] The prepared IrO x The thickness of the gold-plated layer on the titanium mesh surface in the / Pt / Au-Ti mesh hydrogen and oxygen evolution electrode is 1.5μm, the size of the dispersed platinum particles is 0.15μm, and the particle size of the surface iridium oxide is 3.5nm. The electrolysis is used for water electrolysis, and the performance is 1.75V@2A / cm 2 , the concentration of hydrogen in oxygen is 0.65%.
[0039] Example 2
[0040] S1: Take 9.130g of 69% concentrated nitric acid and 0.5g of 40% hydrofluoric acid and dissolve them in 1L of deionized water. The molar ratio of nitric acid to hydrofluoric acid is 10:1. Immerse a 5cm×5cm Ti mesh in the mixed acid for 2min. Then, wash the acid solution on the surface of the Ti mesh with 100mL of deionized water for 3 times and blow dry with argon. Place the Ti mesh with oxide removed in an argon protective atmosphere for standby use.
[0041] S2: Weigh 0.824g of tetrahydrate chloroauric acid and dissolve it in 1L of DMF with a concentration of 2mmol / L, add 13.9g of potassium perchlorate with a concentration of 0.1mol / L to form the first electrolyte solution, then insert the Ti mesh with oxide removed as a cathode into the first electrolyte solution, use a highly graphitized carbon rod as a counter electrode, and use an Ag / AgCl electrode as a reference electrode, and use a constant potential electrodeposition of the first electrolyte solution, with a constant potential of -1.35V vs.Ag / AgCl, and an electrodeposition time of 45min to obtain a titanium mesh Au-Ti mesh with gold plated on the surface;
[0042] S3: Weigh 0.2585g of chloroplatinic acid hexahydrate and dissolve it in 1L of DMF with a concentration of 0.5mmol / L, add 13.9g of potassium perchlorate with a concentration of 0.1mol / L, use Au-Ti mesh as cathode, highly graphitized carbon rod as counter electrode, Ag / AgCl electrode as reference electrode, and use constant potential electrodeposition of the second electrolyte solution. The constant potential is -1.8V vs.Ag / AgCl, and the electrodeposition time is 20min to obtain Pt / Au-Ti mesh with dispersed platinum.
[0043] S4: Weigh 4.07 g of hexahydrated iridium chloride and dissolve it in 1 L of deionized water. The concentration of iridium chloride is 0.01 mol / L. Then adjust the pH value of the solution to 12 with 1 mol / L sodium hydroxide solution. Stir continuously for 60 min to obtain a third electrolyte. Use a gold-plated titanium mesh Pt / Au-Ti mesh with a dispersed platinum distribution as an anode, a highly graphitized carbon rod as a counter electrode, and an Ag / AgCl electrode as a reference electrode. Use a trapezoidal wave potential to electrodeposit the third electrolyte. Control the lower limit potential of the trapezoidal wave to 0.5 V, the upper limit potential to 1.5 V, the voltage rise rate to 0.1 V / s, the upper limit potential constant potential time to 10 s, the lower limit potential constant potential time to 10 s, and the number of trapezoidal wave scanning circles to 100 circles to obtain a gold-plated titanium mesh electrode IrO2 loaded with iridium oxide and dispersed platinum distribution. x / Pt / Au-Ti mesh, that is, IrO x / Pt / Au-Ti mesh hydrogen elimination and oxygen evolution electrode.
[0044] The prepared IrO x The thickness of the gold-plated layer on the titanium mesh surface in the / Pt / Au-Ti mesh hydrogen and oxygen evolution electrode is 2.5μm, the size of the dispersed platinum particles is 0.23μm, and the particle size of the surface iridium oxide is 4.0nm. The electrolysis is used for water electrolysis, and the performance is 1.71V@2A / cm 2 , the concentration of hydrogen in oxygen is 0.36%.
[0045] Example 3
[0046] S1: Take 9.130g of 69% concentrated nitric acid and 0.5g of 40% hydrofluoric acid and dissolve them in 1L of deionized water. The molar ratio of nitric acid to hydrofluoric acid is 10:1. Immerse a 5cm×5cm Ti mesh in the mixed acid for 2min. Then, wash the acid solution on the surface of the Ti mesh with 100mL of deionized water for 3 times and blow dry with argon. Place the Ti mesh with oxide removed in an argon protective atmosphere for standby use.
[0047] S2: Weigh 0.824g of tetrahydrate chloroauric acid and dissolve it in 1L of DMF with a concentration of 2mmol / L, add 13.9g of potassium perchlorate with a concentration of 0.1mol / L to form the first electrolyte solution, then insert the Ti mesh with oxide removed as a cathode into the first electrolyte solution, use a highly graphitized carbon rod as a counter electrode, and use an Ag / AgCl electrode as a reference electrode, and use a constant potential electrodeposition of the first electrolyte solution, with a constant potential of -1.35V vs.Ag / AgCl, and an electrodeposition time of 45min to obtain a titanium mesh Au-Ti mesh with gold plated on the surface;
[0048] S3: Weigh 0.258g of chloroplatinic acid hexahydrate and dissolve it in 1L of DMF with a concentration of 0.5mmol / L, add 13.9g of potassium perchlorate with a concentration of 0.1mol / L, use Au-Ti mesh as cathode, highly graphitized carbon rod as counter electrode, Ag / AgCl electrode as reference electrode, and use constant potential electrodeposition of the second electrolyte solution. The constant potential is -1.8V vs.Ag / AgCl, and the electrodeposition time is 20min to obtain Pt / Au-Ti mesh with dispersed platinum.
[0049] S4: Weigh 20.35g of hexahydrate chloroiridic acid and dissolve it in 1L of deionized water, the concentration of chloroiridic acid is 0.05mol / L, then adjust the pH value of the solution to 12 with 1mol / L sodium hydroxide solution, continue stirring for 60min to obtain a third electrolyte, use platinum dispersed gold-plated titanium mesh Pt / Au-Ti mesh as an anode, a highly graphitized carbon rod as a counter electrode, and an Ag / AgCl electrode as a reference electrode, and adopt trapezoidal wave potential electrodeposition to deposit the third electrolyte, control the lower limit potential of the trapezoidal wave to 0.2V, the upper limit potential to 1.65V, the voltage rise rate to 0.1V / s, the upper limit potential constant potential time to 15s, the lower limit potential constant potential time to 15s, and the number of trapezoidal wave scanning circles to 150 circles, to obtain a platinum dispersed gold-plated titanium mesh electrode IrO loaded with iridium oxide. x / Pt / Au-Ti mesh, that is, IrO x / Pt / Au-Ti mesh hydrogen elimination and oxygen evolution electrode.
[0050] The prepared IrO x The thickness of the gold-plated layer on the titanium mesh surface in the / Pt / Au-Ti mesh hydrogen and oxygen evolution electrode is 2.5μm, the size of the dispersed platinum particles is 0.28μm, and the particle size of the surface iridium oxide is 4.0nm. The electrolysis is used for water electrolysis, and the performance is 1.71V@2A / cm 2 , the concentration of hydrogen in oxygen is 0.29%.
[0051] Example 4
[0052] S1: Take 9.130g of 69% concentrated nitric acid and 0.5g of 40% hydrofluoric acid and dissolve them in 1L of deionized water. The molar ratio of nitric acid to hydrofluoric acid is 10:1. Immerse a 5cm×5cm Ti mesh in the mixed acid for 2min. Then, wash the acid solution on the surface of the Ti mesh with 100mL of deionized water for 3 times and blow dry with argon. Place the Ti mesh with oxide removed in an argon protective atmosphere for standby use.
[0053] S2: Weigh 0.824g of tetrahydrate chloroauric acid and dissolve it in 1L of DMF with a concentration of 2mmol / L, add 13.9g of potassium perchlorate with a concentration of 0.1mol / L to form the first electrolyte solution, then insert the Ti mesh with oxide removed as a cathode into the first electrolyte solution, use a highly graphitized carbon rod as a counter electrode, and use an Ag / AgCl electrode as a reference electrode, and use a constant potential electrodeposition of the first electrolyte solution, with a constant potential of -1.35V vs.Ag / AgCl, and an electrodeposition time of 45min to obtain a titanium mesh Au-Ti mesh with gold plated on the surface;
[0054] S3: Weigh 0.258g of chloroplatinic acid hexahydrate and dissolve it in 1L of DMF with a concentration of 0.5mmol / L, add 10.6g of lithium perchlorate with a concentration of 0.1mol / L, use Au-Ti mesh as cathode, highly graphitized carbon rod as counter electrode, Ag / AgCl electrode as reference electrode, and use constant potential electrodeposition of the second electrolyte solution. The constant potential is -1.8V vs.Ag / AgCl, and the electrodeposition time is 20min to obtain Pt / Au-Ti mesh with dispersed platinum.
[0055] S4: Weigh 20.35g of hexahydrate chloroiridic acid and dissolve it in 1L of deionized water, the concentration of chloroiridic acid is 0.05mol / L, then adjust the pH value of the solution to 12 with 1mol / L sodium hydroxide solution, continue stirring for 60min to obtain a third electrolyte, use platinum dispersed gold-plated titanium mesh Pt / Au-Ti mesh as an anode, a highly graphitized carbon rod as a counter electrode, and an Ag / AgCl electrode as a reference electrode, and adopt trapezoidal wave potential electrodeposition to deposit the third electrolyte, control the lower limit potential of the trapezoidal wave to 0.2V, the upper limit potential to 1.65V, the voltage rise rate to 0.1V / s, the upper limit potential constant potential time to 15s, the lower limit potential constant potential time to 15s, and the number of trapezoidal wave scanning circles to 150 circles, to obtain a platinum dispersed gold-plated titanium mesh electrode IrO loaded with iridium oxide. x / Pt / Au-Ti mesh, that is, IrO x / Pt / Au-Ti mesh hydrogen elimination and oxygen evolution electrode.
[0056] The prepared IrO x The thickness of the gold-plated layer on the titanium mesh surface in the / Pt / Au-Ti mesh hydrogen and oxygen evolution electrode is 2.5μm, the size of the dispersed platinum particles is 0.19μm, and the particle size of the surface iridium oxide is 3.8nm. The electrolysis is used for water electrolysis, and the performance is 1.69V@2A / cm 2 , the concentration of hydrogen in oxygen is 0.08%.
[0057] Example 5
[0058] S1: Take 9.130g of 69% concentrated nitric acid and 0.5g of 40% hydrofluoric acid and dissolve them in 1L of deionized water. The molar ratio of nitric acid to hydrofluoric acid is 10:1. Immerse a 5cm×5cm Ti mesh in the mixed acid for 2min. Then, wash the acid solution on the surface of the Ti mesh with 100mL of deionized water for 3 times and blow dry with argon. Place the Ti mesh with oxide removed in an argon protective atmosphere for standby use.
[0059] S2: Weigh 0.824g of tetrahydrate chloroauric acid and dissolve it in 1L of DMF with a concentration of 2mmol / L, add 13.9g of potassium perchlorate with a concentration of 0.1mol / L to form the first electrolyte solution, then insert the Ti mesh with oxide removed as a cathode into the first electrolyte solution, use a highly graphitized carbon rod as a counter electrode, and use an Ag / AgCl electrode as a reference electrode, and use a constant potential electrodeposition of the first electrolyte solution, with a constant potential of -1.35V vs.Ag / AgCl, and an electrodeposition time of 45min to obtain a titanium mesh Au-Ti mesh with gold plated on the surface;
[0060] S3: Weigh 1.034g of chloroplatinic acid hexahydrate and dissolve it in 1L of DMF at a concentration of 2mmol / L, add 10.6g of lithium perchlorate at a concentration of 0.1mol / L, use Au-Ti mesh as cathode, highly graphitized carbon rod as counter electrode, Ag / AgCl electrode as reference electrode, and use constant potential electrodeposition of the second electrolyte solution. The constant potential is -1.8V vs.Ag / AgCl, and the electrodeposition time is 20min to obtain Pt / Au-Ti mesh with dispersed platinum.
[0061] S4: Weigh 20.35g of hexahydrate chloroiridic acid and dissolve it in 1L of deionized water, the concentration of chloroiridic acid is 0.05mol / L, then adjust the solution pH to 12 with 1mol / L sodium hydroxide solution, continue stirring for 60min to obtain a third electrolyte, use platinum dispersed gold-plated titanium mesh Pt / Au-Ti mesh as an anode, a highly graphitized carbon rod as a counter electrode, and an Ag / AgCl electrode as a reference electrode, and adopt trapezoidal wave potential electrodeposition to deposit the third electrolyte, control the lower limit potential of the trapezoidal wave to 0.2V, the upper limit potential to 1.65V, the voltage rise rate to 0.1V / s, the upper limit potential constant potential time to 15s, the lower limit potential constant potential time to 15s, and the number of trapezoidal wave scanning circles to 150 circles, to obtain a platinum dispersed gold-plated titanium mesh electrode IrO loaded with iridium oxide x / Pt / Au-Ti mesh, that is, IrO x / Pt / Au-Ti mesh hydrogen elimination and oxygen evolution electrode.
[0062] The prepared IrO xThe thickness of the gold-plated layer on the titanium mesh surface in the / Pt / Au-Ti mesh hydrogen and oxygen evolution electrode is 2.5μm, the size of the dispersed platinum particles is 0.49μm, and the particle size of the surface iridium oxide is 4.5nm. The electrolysis is used for water electrolysis, and the performance is 1.73V@2A / cm 2 , the concentration of hydrogen in oxygen is 0.43%.
[0063] Comparative Example 1
[0064] The only difference between this comparative example and Example 4 is that the electrodeposition time in S3 is 120 min, and the other steps and processing conditions are the same.
[0065] Prepared IrO x The thickness of the gold-plated layer on the titanium mesh surface in the / Pt / Au-Ti mesh hydrogen and oxygen evolution electrode is 2.5μm, the size of the dispersed platinum particles is 0.65μm, and the particle size of the surface iridium oxide is 4.7nm. The electrolysis is used for water electrolysis, and the performance is 1.78V@2A / cm 2 , the concentration of hydrogen in oxygen is 0.58%.
[0066] Comparative Example 2
[0067] The only difference from Example 4 is that S3 is not included, that is, the platinum plating step is not included, and the other steps and processing conditions are the same.
[0068] Prepared IrO x / Au-Ti mesh hydrogen and oxygen evolution electrode has a gold layer thickness of 2.5μm on the titanium mesh surface and a particle size of 8.5nm of iridium oxide on the surface. The electrolysis was used for water electrolysis and the performance was 1.86V@2A / cm 2 , the concentration of hydrogen in oxygen is 1.33%.
[0069] The electrode performances obtained from the above embodiments and comparative examples are summarized, and the experimental data are summarized in the following table:
[0070] <![CDATA[Performance V@2 A / cm 2 > Hydrogen concentration in oxygen Example 1 1.75 0.65% Example 2 1.71 0.36% Example 3 1.71 0.29% Example 4 1.69 0.08% Example 5 1.73 0.43% Comparative Example 1 1.78 0.58% Comparative Example 2 1.86 1.33%
[0071] It can be seen from Table 1 above that, compared with Comparative Examples 1 and 2, the hydrogen evolution electrodes prepared in Examples 1 to 5 all showed better hydrogen removal effects, and the hydrogen removal effects were related to the size and distribution of the platinum particles.
[0072] In Comparative Example 2, for the titanium mesh electrode not plated with platinum, the hydrogen concentration in the oxygen produced by the anode is the highest, indicating that Pt plays an important role in hydrogen removal at the anode.
[0073] Figure 1This is the trapezoidal wave potential program diagram of platinum-dispersed gold-plated titanium mesh electrodeposited with iridium oxide. By controlling the upper and lower limit potentials and the number of scanning circles, electrodes with different iridium oxide particle sizes can be obtained.
[0074] Figure 2 The oxygen evolution polarization performance of the electrodes of Example 4 and Comparative Example 1 shows that the voltage of the platinum-plated electrode (Example 4) is higher than that of the electrode without platinum plating (Comparative Example 1) at 2 A / cm 2 The 17 mV decrease at current density indicates a higher efficiency, which may be due to the increased overall conductivity and improved distribution of iridium oxide caused by platinum plating;
[0075] Figure 3 The percentage of hydrogen in the anode oxygen of each embodiment and comparative example during water electrolysis shows that the hydrogen content in the oxygen of the platinum-plated electrode is lower than that of the electrode not plated with platinum, and excessive platinum particle size (Comparative Example 1) will also lead to poor hydrogen removal function of the electrode.
[0076] In summary, the hydrogen-dissipating and oxygen-evolving electrodes provided in the embodiments of the present application, their preparation methods, and their application schemes in water electrolysis, have at least the following beneficial effects:
[0077] The dehydrogenation function is constructed by plating gold and platinum on the surface of the titanium mesh. Plating the gold layer on the Ti surface first is beneficial to improving the high-potential oxidation resistance of the Ti mesh. At the same time, gold plating can further improve the conductivity of the electrode and reduce the interface impedance. The platinum particles dispersed on the surface of the Au layer mainly function to dehydrogenate.
[0078] The basic principle is that when the hydrogen diffused from the cathode to the anode passes through the titanium mesh together with the oxygen, the hydrogen and oxygen will directly produce water by catalytic reaction on the platinum surface, consuming the hydrogen, thereby achieving the purpose of reducing the hydrogen in the oxygen. This avoids adding platinum directly to the PEM membrane or to the catalyst layer. Since the direct reaction of hydrogen and oxygen on the platinum surface will release heat, long-term operation will cause a significant attenuation of the membrane and catalyst layer. At the same time, iridium oxide on the gold and platinum surfaces helps to enhance the IrO x conductivity, thereby improving the oxygen evolution activity and durability of the catalyst.
[0079] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a hydrogen-evolving and oxygen-consuming electrode, characterized in that: The specific process of the preparation method of the hydrogen consumption and oxygen evolution electrode is as follows: S1: Titanium mesh surface pretreatment The titanium mesh is placed in a mixed acid solution and soaked for 1 to 5 minutes, taken out after soaking, the acid solution on the surface is washed off with deionized water, and the cleaned titanium mesh is placed in an argon atmosphere to obtain a titanium mesh after surface pretreatment; S2: Titanium mesh gold-plated Chloroauric acid is dissolved in dimethylformamide (DMF), and a perchlorate with a concentration of 0.1 to 0.5 mmol / L is added to obtain a first electrolyte solution. The titanium mesh with surface pretreatment in S1 is used as a cathode, a highly graphitized carbon rod is used as a counter electrode, and an Ag / AgCl electrode is used as a reference electrode. The first electrolyte solution is deposited by constant potential electrodeposition to obtain a titanium mesh Au-Timesh with gold on the surface. S3: Gold-plated titanium mesh with platinum diffusion Dissolve chloroplatinic acid in dimethylformamide (DMF), and add perchlorate with a concentration of 0.1-0.5 mol / L to obtain a second electrolyte solution, use the gold-plated titanium mesh Au-Timesh prepared by S2 as a cathode, a highly graphitized carbon rod as a counter electrode, and an Ag / AgCl electrode as a reference electrode, and adopt constant potential electrodeposition of the second electrolyte solution to obtain a gold-plated titanium mesh Pt / Au-Timesh with dispersed platinum distribution; S4: Surface coating with iridium oxide Dissolve chloroiridic acid in deionized water to obtain a chloroiridic acid solution with a concentration of 0.01-0.1 mol / L, then adjust the pH value to 10-14 with sodium hydroxide with a concentration of 1 mol / L, and continue stirring for 30-90 min to obtain a third electrolyte. Use the gold-plated titanium mesh Pt / Au-Ti mesh with platinum dispersed distribution prepared by S3 as an anode, a highly graphitized carbon rod as a counter electrode, and an Ag / AgCl electrode as a reference electrode. Use a trapezoidal wave potential to perform electrodeposition treatment of the third electrolyte, control the upper and lower limits of the potential and the number of scanning cycles, and obtain a gold-plated titanium mesh electrode IrO2 loaded with platinum dispersed distribution and iridium oxide. x / Pt / Au-Ti mesh, that is, IrO x / Pt / Au-Timesh hydrogen elimination and oxygen evolution electrode, the prepared IrO x The thickness of the gold-plated layer on the titanium mesh surface in the / Pt / Au-Timesh hydrogen-dissipating and oxygen-evolving electrode is 1-5 μm, the size of the dispersed platinum particles is 0.1-2 μm, and the size of the surface iridium oxide particles is 2-10 nm.
2. The method for preparing a hydrogen-consuming and oxygen-evolving electrode according to claim 1, characterized in that: The mixed acid solution in S1 is a mixed solution of nitric acid and hydrofluoric acid, the molar ratio of nitric acid to hydrofluoric acid is 1:1 to 10:1, and the hydrogen ion concentration in the mixed acid is 0.1 to 0.5 mol / L.
3. The method for preparing a hydrogen-consuming and oxygen-evolving electrode according to claim 1, characterized in that: The concentration of chloroauric acid in DMF in S2 is 0.5-5 mmol / L.
4. The method for preparing a hydrogen-consuming and oxygen-evolving electrode according to claim 1, characterized in that: The perchlorate in S2 is one or more of potassium perchlorate, sodium perchlorate and lithium perchlorate.
5. The method for preparing a hydrogen-consuming and oxygen-evolving electrode according to claim 1, characterized in that: The constant potential electrodeposition parameters in S2 are: potential -1.2 to -1.5 V vs. Ag / AgCl, and electrodeposition time is 30 to 60 min.
6. The method for preparing a hydrogen-consuming and oxygen-evolving electrode according to claim 1, characterized in that: The concentration of chloroplatinic acid in DMF in S3 is 0.1-2 mmol / L.
7. The method for preparing a hydrogen-consuming and oxygen-evolving electrode according to claim 1, characterized in that: The perchlorate in S3 is one or more of potassium perchlorate, sodium perchlorate and lithium perchlorate.
8. The method for preparing a hydrogen-consuming and oxygen-evolving electrode according to claim 1, characterized in that: The constant potential electrodeposition parameters in S3 are: potential -1.5 to -1.8 V vs. Ag / AgCl, and electrodeposition time is 10 to 30 min.
9. The method for preparing a hydrogen-consuming and oxygen-evolving electrode according to claim 1, characterized in that: The lower limit potential range of the trapezoidal wave in S4 is 0.1-0.5V, the upper limit potential range is 0.8-1.8V, the voltage rise rate is 0.02-0.2V / s, the upper and lower limit potential constant potential time is 5-30s, and the number of trapezoidal wave scanning circles is 50-200 circles.
10. An application of a hydrogen consumption and oxygen evolution electrode, characterized in that: The hydrogen-eliminating and oxygen-evolving electrode is used for electrolyzing water.